2013
DOI: 10.3390/s130202196
|View full text |Cite
|
Sign up to set email alerts
|

Monolithically Integrated Mid-Infrared Quantum Cascade Laser and Detector

Abstract: Abstract:We demonstrate the monolithic integration of a mid-infrared laser and detector utilizing a bi-functional quantum cascade active region. When biased, this active region provides optical gain, while it can be used as a detector at zero bias. With our novel approach we can measure the light intensity of the laser on the same chip without the need of external lenses or detectors. Based on a bound-to-continuum design, the bi-functional active region has an inherent broad electro-luminescence spectrum of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…For this, we use a bi-functional quantum cascade laser/detector (QCLD) active region13. The capability of both generating and detecting mid-infrared light with the same epilayer structure, simply by changing the applied bias, makes this bi-functional structure an ideal candidate for monolithic devices14. We have significantly improved the performance of the active region by further optimization to prevent thermal back-filling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, we use a bi-functional quantum cascade laser/detector (QCLD) active region13. The capability of both generating and detecting mid-infrared light with the same epilayer structure, simply by changing the applied bias, makes this bi-functional structure an ideal candidate for monolithic devices14. We have significantly improved the performance of the active region by further optimization to prevent thermal back-filling.…”
Section: Resultsmentioning
confidence: 99%
“…The inset shows the time-resolved detector signal of a single pulse at the maximum laser output power. In order to minimize the electric crosstalk between the laser and the detector, we use separated contacts14 instead of a shared bottom side contact. With a laser power of 200 mW at room temperature (pulse average), we have observed a detector signal of 150 mV into 50 Ω (without amplifier).…”
Section: Resultsmentioning
confidence: 99%
“…12 We have demonstrated that the coherent light source and detector, operating at the same frequencies, can be integrated on a single chip using the specifically designed heterostructure material and the same fabrication procedure. 13 This approach has the potential to serve as a basic building block of a new kind of integrated sensors.…”
mentioning
confidence: 99%
“…In order to minimize electric crosstalk via a shared series resistance, adjacent contacts in the trenches beside the ridges were used, instead of a standard back side substrate contact. 13 The top and bottom contacts were formed by sputter deposition of 10 nm of titanium and 250 nm of gold. On the back facets of the lasers and the detectors, a high reflection coating consisting of SiN x and gold was applied to increase the light power and the detector absorption.…”
mentioning
confidence: 99%
“…In contrast to cleaved devices, the bottom contact can extend beyond the etched facet, allowing the fabrication of laser ridges distant to the chip edge, enabling for example the monolithic integration of THz QCLs and detectors, which is important for the development of a system on a chip technology. 9,10 Here, we investigate the influence of cleaved and etched facets on the device performance. We show theoretically and experimentally that the reflectivity depends on the facet type, leading to different mirror losses.…”
mentioning
confidence: 99%